A Perceptual Leadership Style for The Philippine Airline Management: An Initial Survey - Rioveros, Gilmore M. (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The research was an initial survey of the diverse types of leadership used by notable people across the globe. This qualitative study analyzed these leadership styles and the relevance of leadership at work. There were several styles listed, but the researcher has found one style to be appropriate in the management of the Philippine Airlines. This study utilizes observation and documentary analysis. As a result of this paper, it was found out that the best model for leadership that can be used is the transformational model which is also the leadership of the transition or transformational leadership. In order to confirm its usefulness and relevance for the good of the organization or business, the researcher will prefer to perform an extensive analysis on transformational leadership in the future.